The Contribution of Regenerative Endodontics in the Management and Healing of Pathological Root Resorptions: A Systematic Review - BelHaj Salah, Kawther; Jaafoura, Sabra; Mechri, Ghaith Abdallah; Gnaba, Imen; Youssef, Souha Ben (European Journal of General Dentistry, 2025)
Pathological root resorption is an irreversible condition that can compromise the tooth's prognosis. Despite the success of conventional root canal treatment, these methods have their limitations and cannot restore damaged dental tissue. Recently, regenerative techniques have been employed to treat pathological root resorption.The aim of this systematic review is to evaluate the role of regenerative endodontics in managing pathological internal and external root resorptions in permanent teeth.A literature search was conducted on the following databases: MEDLINE via PubMed, Web of Science, Cochrane, and Scopus, using the following Medical Subject Headings (MeSH) « root resorption », « regenerative endodontics », and keywords « tooth resorption » and « Platelet-Rich Fibrin ». A reading grid was established to extract data related to the research question. The methodological quality of each included study was assessed using Cochrane RoB and Newcastle–Ottawa scale. The review protocol was registered with PROSPERO (identification N° CRD420251023900).After applying inclusion and exclusion criteria, nine articles were included in our review. These studies examined clinical data related to the type and location of root resorption, as well as data related to the regenerative endodontic technique employed, and the type of repair. The risk of bias was low in one study and moderate in eight studies.The selected studies highlighted the effectiveness of regenerative endodontic techniques based on platelet-rich fibrin and revascularization in the treatment of internal and external resorptions, demonstrating their ability to repair resorption defects through the formation of newly calcified tissue.
Keywords: root resorption; platelet-rich fibrin; revascularization; regenerative endodontics